Distributional Effects of Surging Housing Costs under Schwabe`s Law of Rent - Thomas Steger; Volker Grossmann; Benjamin Larin; Hans Torben Löfflad (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The upward sloping trend of rents and house prices has initiated a debate on the consequences of surging housing costs for wealth inequality and welfare. We employ a frictionless two-sectoral macroeconomic model with a housing sector to investigate the dynamics of wealth inequality and the determinants of welfare. Households have non-homothetic preferences, implying that the poor choose a higher housing expenditure share, being compatible with Schwabe's Law of Rent. We examine at first the isolated effects of increasing housing costs in partial equilibrium. The model is closed by introducing a production sector that enables us to analyze the general equilibrium consequences of a widely discussed policy option that aims at dampening the growth of housing costs. Abolishing zoning regulations triggers a slower rent growth and reduces wealth inequality by about 0.7 percentage points (measured by top 10 percent share). Average welfare increases by about 0.5 percent. However, the household-specific welfare effects are clearly asymmetric. The poor benefit more than the rich. The richest wealth decile is even worse off.
Keywords: E10; E20; O40; 330; Macroeconomics and Housing; Long-Term Growth; Schwabe's Law of Rent; Wealth Inequality; Welfare